The Effect of Manure Cow Fertilizer and Super Natural Nutrition Foliar Fertilizer on the Growth and Yield of Tomato (Lycopercicum esculentum Mill.) Tymoti Variety - Pono dan Abdul Rahmi . (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2017)
This experiment aims to: (1) to study of the effect of manure cow fertilizer and Super Natural Nutritionfoliar fertilizeras well as their interaction on the growth and yield of tomato plants; and (2) to find proper dosage of manure cow fertilizer and proper concentration of Super Natural Nutritionfoliar fertilizer for better growth and yield of tomato plants.The research carried out from February 2016 to April 2016, in the Village of Suka Rahmat Melak, Teluk Pandan Subdistrict, East Kutai District.  It applied Completely Randomized Block Design with factorial experiment 4 x 4 and three replications.  The first factor is the dosage of the manure cow fertilizer (P) consists of 4 levels, namely: no manure cow fertilizer application (p0), 5 Mg ha ̵ ¹, or 2kg plot ̵ ¹ (p1), 7,5 Mg ha ̵ ¹ or 3kg plot ̵ ¹ (p2), and 10 Mg ha ̵ ¹ or 4kg plot ̵ ¹   (p3). The second factor is the concentration of Super Natural Nutritionfoliar fertilizer (N) consists of 4 levels: without Super Natural Nutritionfoliar fertilizer (n0), 1 ml 1 ̵ ¹water (n1), 2 ml 1 ̵ ¹ water (n2), and 3 ml 1 ̵ ¹  water (n3).Result of the research revealed that : (1) application of manure cow fertilizer was affected significant to very significantly on plant height at 14, 28, and 42 days after planting, days of plant flowered, days of plant harvest,  the number of fruits per plant, weight of fruit per plant, and production of fruit. The highest production is attained by the 10 Mg ha-1 fertilizer manure cow fertilizer (p3), namely 31,15 Mg ha-1, In reverse, the least production is attained by without manure cow fertilizer (p0), namely 21,28 Mg ha ̵ ¹; (2) application of Super Natural Nutrition foliar fertilizer was significantly to very significantly on the plant height at 14, 28, and 42 days after planting, days of plant flowered, days of plant harvest,  the number of fruits per plant, weight of fruit per plant, and production of fruit. The highest production is attained by the 3 ml l-1 water (n3), namely 31,75 Mg ha-1, In reverse, the least production is attained by without Super Natural Nutrition foliar fertilizer (n0), namely 23,27 Mg ha ̵ ¹; and (3) interaction between manure cow fertilizer and Super Natural Nutrition foliar fertilizer was affected significantly to very significantly on the plant height at 28 and 42 days after planting, number of fruit per plant, and fruit weight per plant, but no significantly on the plant height at 14 days after planting, days of plant flowered, days of plant harvest,  and producton of fruit.